Interaction of waves with a body floating on polynya between two semi-infinite ice sheets - Li, ZF; Shi, YY; Wu, GX (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2018)
The interaction of waves with a two-dimensional body floating on polynya between two semi-infinite ice sheets is investigated, based on a hybrid method utilizing a simple source function and eigenfunction matching. The ice sheet is modelled as a continuous thin elastic plate with uniform properties, while the fluid flow is described by the velocity potential. In the polynya, an integral equation is established by using the simple source function. In the two exterior ice covered regions, the potential is expanded in terms of eigenfunctions which satisfy the governing equation and all boundary conditions apart from that on the interface with the inner region. The unknown coefficients in the expansion and the boundary integral equation in the inner region are solved together by enforcing the continuity conditions of the pressure and normal velocity on the interface. The effectiveness and accuracy of the hybrid method is demonstrated through comparison with published results for a submerged cylinder and a floating rectangular body. Simulations are then carried out for a floating elliptical cylinder. Extensive results for the hydrodynamic force and motion response are provided, and the effects of ice draught as well as the body shape are investigated.